SAT0575 Ra Patients' Expectations of Treatment - Comparison with the Result of Surveys in Multi-Cohort-. (10th June 2014) - Sagawa, A.; Funahashi, K.; Matsubara, T.; Izumihara, T.; Adachi, M.; Iwahasi, M.; Oyama, T.; Nishioka, Y.; Hashimoto, K.; Oribe, M.; Takahashi, Y.
Abstract : Background: To execute "Treat to Target's (T2T)" primary principal, it is very important to understand the extent of patient education and patients' understanding thereof, but these factors are not well understood. Objectives: To better understand T2T implementation, a large- scale survey was conducted using a multi-cohort study in Japan. Methods: An anonymous survey was given to 9487 RA outpatients in multiple facilities in multiple locations in Japan. The contents included; age, gender, medical history, and comments on: 1) things they wished to know before administration, 2) expectations of medication, 3) disappointment with medication and its causes, 4) anxiety switching medication 5) biologics experience, 6) goals for treatment, 7) satisfaction level, 8) questions for and expectation of doctors, 9) treatment fees, 10) impression of biologics, 11) impressions of injections, 12) opinions regarding their ideal treatment (multiple choice and essay). For further analysis the total results from respondents were divided into 2 groups; Biologics (BG), 3363 patients, and DMARDs Group (DG), 4535patients. The patients were also separated into 6 groups by region to determine any regional differences. Results: Eighty-three percent of the respondents were female, with a distribution of 77% DG and 33% BG. For "expectations of medication", both groups expected reliable efficacy, BG (36%) and DG (39%), with little difference in this regard. For "Experience of disappointment", BG (35%) was twice that of DG (19%); the main reason for disappointment for BG was diminishing efficacy; however, for DG it was adverse events. The reason for "anxiety when switching" was mainly "adverse events", but the response rate of "diminishing efficacy" was higher in BG, related with the reason for disappointment. In both groups the "goals for treatment" were mostly "the improvement of QOL" and "reduced destruction/deformation of joints", but "reduced destruction/deformation of joints" for BG were about 1.5 times that of DG. For injections, regarding DG there were more "troublesome" or "frightening" responses, but nearly half the BG group responded that "self-injection" is convenient. There was not much regional variation in the responses to the questionnaire in the six areas. However, in areas in which the patients use more biologics, although patients experience disappointment with secondary failure and anxiety regarding the expense of treatment, they nevertheless had expectations of suppression of joint destruction. It was noted that patient background regarding medication usage was different by area. Conclusions: RA patients in Japan hold expectations for medication in terms of assured improvement in their condition. The patients in BG, due to knowledge of prevention of joint destruction, have higher treatment goals than DG. The comparison between 2 groups indicated once patients experience high efficacy, they can tolerate self-injection and higher fees. Our study indicates Japanese RA patients going to the RA special facility receiving the same level T2T, but BG and DG are not at the same level of achievement in all 51 facilities. These results indicated we have to conduct further patient education for DG. References: Clin Rheumatol, NOV31(11), 1559-66, 2012. Disclosure of Interest: A. Sagawa: None declared, K. Funahashi: None declared, T. Matsubara Grant/research support: Astelas pharm.co., Santen Pharm.Co., Ltd, Janssen Pharm.K.K, Eisai Co., Ltd, Abbvie GK, Chugai Pharm Co., Ltd, Bristorl-Myers K.K, Mitsubishi Tanabe Pharm co., Ltd, T. Izumihara: None declared, M. Adachi: None declared, M. Iwahasi: None declared, T. Oyama: None declared, Y. Nishioka: None declared, K. Hashimoto: None declared, M. Oribe: None declared, Y. Takahashi: None declared DOI: 10.1136/annrheumdis-2014-eular.2545